PENDIDIKAN SPIRITUAL PADA ANAK USIA DINI Upaya Penggalian Narasi edukatif al-Quran Dalam Pembinaan Rasa Keagamaan Pada Anak - Rohimin Rohimin (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This paper aims to explore and elaborate narrative-educational of al-Quran about giving the direction of spiritual education of early childhoodmethodology. Spirituality education in early childhood is a spirituality education without tariqah, suluk, maqam, and murshid. Spiritual education developed in early childhood is a spiritual education that is dzauqiyah, that is spirituality that is perceived and not rationalized spirituality. Spiritual education is basically building and developing the potential divine nature that has been conferred on every human being. The building of spiritual education is the immunization of human beings in order to stay awake and preserved in the circle of homosex- ual religious, that is the man who covered with religion. From the very beginning creation of man, the Qur’an provides an educative narrative in order to establish and develop a sense of religion, especially in early childhood. This religious sense in turn will provide endurance for humans in tracing its life cycle. Spiritual education through the guidance of religious sense in early childhood is seen as a glorious time to stimulate the nature of the divine instincts that already exist in each child. Keywords: Spiritual education, early childhood, narrative-educational, and al-Quran